Hubungan Word Of Mouth Communication di Instagram terhadap Minat Beli Konsumen - Giszela Deviona; Ferry Darmawan (UNISBA Press, 2023)
Abstract. Advances in communication technology also affect marketing techniques or methods, namely buzz marketing which is a word of mouth technique which is now not only limited to face-to-face communication but is already in electronic word of mouth. This study is entitled